ANALYSIS ON DYNAMIC CHARACTERISTICS OF TOOTH ROOT CRACK OF GEAR DRIVE SYSTEM UNDER VARIABLE LOAD EXCITATION - SHI PeiMing; ZHAO Na; LIANG Kai; HAN DongYing (Jixie qiangdu)
According to the characteristics that crack can cause changes in mesh stiffness,the four degree of freedom dynamic model of the single-stage gear transmission system with the gear crack fault is established and the nonlinear dynamic mechanism of crack fault is studied. The Runge-Kutta numerical method was used to simulate and analysis crack fault. The characteristics of the crack signal are studied by using the time-frequency analysis method,which provides a theoretical support for the gear crack fault diagnosis. On this basis,the dynamic characteristics of gear crack under variable load excitation are analyzed. Analysis shows that,under variable load excitation,the vibration wave forms are very similar to the variable load excitation; Cracks caused by the impact phenomenon on the waveform and meshing frequency and its harmonics appear sideband.Sideband spectrum of the meshing frequency is the rotating frequency of the fault gear; Under variable load excitation,the frequency components of the low frequency is related to the variable load excitation.